EKSISTENSI RERAJAHAN SEBAGAI MANIFESTASI MANUNGGALNYA SENI DENGAN RELIGI - I Wayan Sudana (FBS UNY, 2009)
Rerajahan is one of Bali culture product that was axist since prahindu period, but until today still exist and eternal. The existence and conservation rerajahan in Bali because of support from several culture institute that was good not only private institute (traditional) but also goverment institutes. The commitment of that institutes to keep the existence of rerajahan, because the meaning and the function still relate with social community life. Rerajahan formed a picture and written and has symbolic meaning, that believed have spiritual power or magical power and have a great effect. In the other hand, visually, the figurs and motives in rerajahan is very expressive, inspirative, and has aesthetics quality. Therefore, rerajahan have two values. There are religious value and aesthetics value, that believe as one of manifestation the singleness of art and religion. Keywords: rerajahan, art and religion